Leader‐signaled knowledge hiding: Effects on employees' job attitudes and empowerment. (11th January 2019) - Offergelt, Florian; Spörrle, Matthias; Moser, Klaus; Shaw, Jason D.
Summary: The authors introduce the concept of leader‐signaled knowledge hiding (LSKH) and conduct two studies observing what happens when leaders signal employees that knowledge hiding (KH) is practiced, tolerated, and expected. Social learning theory provides the basis for predicting that LSKH encourages subordinates to hide knowledge, even though they suffer from negative job attitudes in reaction. In Study 1, data measured at two time points ( N  = 1, 162) shows that LSKH positively predicts KH among subordinates. The KH dimensions of evasive hiding and playing dumb (but not rationalized hiding) negatively relate to job satisfaction and positively affect turnover intentions. Study 2 ( N  = 1, 169) replicates these results with cross‐sectional data. Moreover, Study 2 demonstrates that evasive hiding and playing dumb negatively affect empowerment, whereas rationalized hiding has a positive effect. Both studies reveal that subordinates will show less KH when they work under leaders who avoid LSKH and in turn have more job satisfaction, feel more empowered, and harbor fewer turnover intentions. The results in this study provide important practical implications for knowledge management activities.